2022
DOI: 10.3389/fcvm.2021.765422
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Load: An Effective Indicator of Systemic Circulation Status in Individuals With Acute Altitude Sickness

Abstract: Background: Acute high altitude (HA) exposure results in blood pressure (BP) variations in most subjects. Previous studies have demonstrated that higher BP is potentially correlated with acute mountain sickness (AMS). The BP load may be of clinical significance regarding systemic circulation status.Objectives: This study aimed to examine HA-induced BP changes in patients with AMS compared to those in healthy subjects. Further, we provided clinical information about the relationship between variations in 24-h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…More recently, cardiac function parameters at sea level were used as predictors of HAHD occurrence by screening echocardiographic parameters of the left ventricle, right ventricle, and pulmonary circulation ( 29 ). Moreover, changes in blood pressure (BP) and BP load were clinically found to be higher in HAHD patients, suggesting that BP load can be an effective indicator to evaluate cardiovascular adaptation ability ( 30 ). Furthermore, study found subjects with low 25% of the pulmonary volume values at low altitude were shown to be susceptible to high levels of pulmonary arterial pressure ( 31 ).…”
Section: High-altitude Heart Diseasesmentioning
confidence: 99%
“…More recently, cardiac function parameters at sea level were used as predictors of HAHD occurrence by screening echocardiographic parameters of the left ventricle, right ventricle, and pulmonary circulation ( 29 ). Moreover, changes in blood pressure (BP) and BP load were clinically found to be higher in HAHD patients, suggesting that BP load can be an effective indicator to evaluate cardiovascular adaptation ability ( 30 ). Furthermore, study found subjects with low 25% of the pulmonary volume values at low altitude were shown to be susceptible to high levels of pulmonary arterial pressure ( 31 ).…”
Section: High-altitude Heart Diseasesmentioning
confidence: 99%
“…Increased sympathoadrenal activity has been implicated in the pathogenesis of AMS; during an 8-h exposure to normobaric hypoxia (12% O 2 , equal to 4,600 m) subjects who developed AMS had significantly higher arterial epinephrine concentrations ( Kamimori et al, 2009 ). In addition, individuals with AMS, and not those without AMS, had higher BP levels and BP load changes after an ascent to 3,700 m altitude ( Chen et al, 2022 ). In this study, excessive BP load variations are associated with AMS, and BP load was suggested to be an effective indicator of systemic circulation status in AMS patients.…”
Section: Physiological and Cognitive Responses To Systemic Environmen...mentioning
confidence: 99%